Mapping Knowledge Domain to Analyze the Building Information Modeling on Building Energy Saving Based on Visualized Analysis Method - Gen Li; Haining Tian (Advances in Civil Engineering)
Building information modeling (BIM), as a novel knowledge field of modern engineering management, is bringing different degrees of changes to the construction industry from engineering practice to management concept. In order to analyze the research status of BIM in the field of energy-saving transformation, find its research hotspots, and reveal its future development trend to guide the practice and application of building information model better, the mapping knowledge domain is constructed via the literature visualization analysis method based on the theory of cocitation analysis and the pathfinder algorithm This is to analyze the hot spots and reveal the frontier of building information modeling on building energy saving. This article lists journal articles and review articles included in the web of science database between 2012 and 2022, using the literature visualization analysis software Citespace to establish the knowledge graph of the collected literature, the scholars’ collaboration analysis, the research institutions’ collaboration analysis, the national collaboration analysis, the keyword co-occurrence analysis, the keyword cluster analysis, the time zone analysis, the keywords timeline analysis, and the literature cocitation analysis have been carried out and discussed. According to the analysis results, the research hotspots and future development trends are interpreted and discussed.